Qualitative study of perceptions of factors contributing to success or failure among participants in a US weight loss trial of financial incentives and environmental change strategies - Kevin G Volpp; Justin Clapp; Karen Glanz; Collin Kather; Annie Chung; Ji Rebekah Choi (BMJ Open)
Background The use of financial incentives and environmental change strategies to encourage health behaviour change is increasingly prevalent. However, the experiences of participants in incentive interventions are not well characterised. Examination of participant perceptions of financial incentives and environmental strategies can offer insights about how these interventions are facilitating or failing to encourage behaviour change.Objective This study aimed to learn how participants in a randomised trial that tested financial incentives and environmental interventions to support weight loss perceived factors contributing to their success or failure in the trial.Design Qualitative study with one-time interviews of trial participants with high and low success in losing weight, supplemented by study records of incentive payments and weight loss.Participants 24 trial participants (12 with substantial weight loss and 12 with no weight loss) stratified equally across the 4 trial arms (incentives, environmental strategies, combined and usual care) were interviewed.Analytical approach Transcribed interviews were coded and interpreted using an iterative process. Explanation development was completed using an abductive approach.Results Responses of trial participants who were very successful in losing weight differed in several ways from those who were not. Successful participants described more robust prior attempts at dietary and exercise modification, more active engagement with self-limitations, more substantial social support and a greater ability to routinise dietary and exercise changes than did participants who did not lose weight. Successful participants often stated that weight loss was its own reward, even without receiving incentives. Neither group could articulate the details of the incentive intervention or consistently differentiate incentives from study payments.Conclusions A number of factors distinguished successful from unsuccessful participants in this intervention. Participants who were successful tended to attribute their success to intrinsic motivation and prior experience. Making incentives more salient may make them more effective for participants with greater extrinsic motivation.Trial registration number NCT02878343